ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI SELF-CONFIDENCE SISWA SMK KATOLIK St. YOSEPH SOA - Maria Irvania Dede; Ariswan Usman Aje; Finsensius Yesekiel Naja (Program Studi Pendidikan Matematika, 2022)
This study aims to determine how the mathematical problem-solving abilities of MA/SMA/SMK students in terms of self-confidence of students who focus on trigonometry material. This research is qualitative research with a descriptive method. The subjects in this study were students of class X SMK Catholic St. Joseph Soa. The sampling technique used is the purposive sampling technique. Data collection techniques in this study were tests, questionnaires and interviews. The research instrument used was a test of mathematical problem-solving ability in the form of descriptions, self-confidence questionnaires and interview sheets. The data analysis technique uses questionnaire analysis, questions, interviews and data analysis (data reduction, data presentation, and conclusions). The results showed that the self-confidence of the tenth graders of SMK Catholic St. Yoseph Soa is divided into three, namely high, medium and low. The mathematical problem-solving ability of students with a high level of self-confidence is able to meet the four problem-solving indicators according to Polya. The mathematical problem-solving ability of students with moderate self-confidence is only able to meet indicators 1, 2 and 3. The problem-solving ability of students with low self-confidence is not able to meet the four problem-solving indicators according to Polya.